Unveiling the therapeutic potential of phenolic compounds from Boletus edulis in osteoarthritis treatment - Mónica Paesa; Mauricio David Izquierdo; Cristina Remírez de Ganuza; Pedro Ferreira-Santos; María Jesús Rodríguez-Yoldi; Gracia Mendoza (Scientific Reports)
Abstract Osteoarthritis (OA) is a joint disease characterized by inflammation, cartilage degeneration, and pain. Recent studies have focused on the potential of active phenolic compounds as a treatment for OA, owing to their anti-inflammatory, antioxidant, and chondroprotective effects. Specifically, Boletus edulis (BE) extracts, a natural product from mushrooms, have been shown as significantly active compounds against oxidative stress and inflammation. Our aim was to evaluate the anti-inflammatory and chondroprotective potential of BE extracts, primarily composed of phenolic compounds and flavonoids, in OA in vitro models. Our results showed that cell treatment with 250 µg/mL of BE extracts maintained cell viability above 70% without affecting apoptosis or cell cycle. At the molecular level, BE extracts exerted anti-inflammatory effects by reducing nitric oxide (NO) levels, as well as the expression of inducible nitric oxide synthase (iNOS) and pro-inflammatory cytokines and chemokines (interleukin-6 (IL-6), IL-8, (C-X-C motif) ligand 1 (CXCL-1)) in lipopolysaccharide (LPS)-stimulated cells. Additionally, BE extracts treatment demonstrated a significant decrease in matrix metalloproteinases 3 and 13 (MMP-3, MMP-13) expression, while avoiding the depletion in the expression of chondrogenic markers, aggrecan and collagen II. Furthermore, inflammation was also significantly reduced through the inhibition of p65 nuclear translocation. These findings suggest that BE extracts may provide a promising basis for the development of novel therapeutic strategies in the treatment of OA, reducing inflammation and chondrocytes damage.